Health professionals’ perception of appropriateness of care: a qualitative study in Italian pediatric hospices - Cappi, Valentina; Riboni, Serena; Grana, Marianna; Pierotti, Emanuela; Ravelli, Andrea; Sutti, Stefania; Testa, Sara; Spacci, Alessio; Artioli, Giovanna; Sarli, Leopoldo; Pellegatta, Federico (Acta Biomedica Atenei Parmensis, 2020)
Background: Appropriateness is particularly relevant in palliative care, an area in which it is essential to question the real need for treatments. Few studies explored the perception of appropriateness by professionals in pediatric palliative care, revealing the conflict sometimes faced when confronted with the uncertainty of prognosis and end-of-life decisions. Aims: The objective of this study is firstly to investigate the perception that doctors, nurses and psychologists, operating in Italian pediatric hospices, have of the appropriateness of the care they provide. Secondly, to understand what repercussions the perception of non-appropriateness has at individual and team level. Methods: A qualitative study was conducted between 2019 and 2020 through semi-structured interviews with a convenience sample of 17 professionals working it Italian pediatric hospices. Results: The interviewees do not refer to a common concept of appropriateness, but compare the latter to: the quality of life, the global care of the assisted person, the proportionality of care, the early recognition of the need for palliative care. The discussion within the team emerges as a privileged place to manage the discomfort of individual professionals in the face of treatment choices in conflict with their own values. Conclusion: the non-referring to a univocal conception of appropriateness deprives professionals of an objective criterion to resolve the most difficult decisions. However, it allows them to establish what from time to time seems to be the most appropriate care pathway for a given patient, at a given time and context, preserving the goal of personalized care.